2020
DOI: 10.1126/sciadv.abb1989
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structures of NPC1L1 reveal mechanisms of cholesterol transport and ezetimibe inhibition

Abstract: The intestinal absorption of cholesterol is mediated by a multipass membrane protein, Niemann-Pick C1-Like 1 (NPC1L1), the molecular target of a cholesterol lowering therapy ezetimibe. While ezetimibe gained Food and Drug Administration approval in 2002, its mechanism of action has remained unclear. Here, we present two cryo–electron microscopy structures of NPC1L1, one in its apo form and the other complexed with ezetimibe. The apo form represents an open state in which the N-terminal domain (NTD) interacts l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 67 publications
(93 reference statements)
6
65
0
Order By: Relevance
“…A bibliographic search of the main ezetimibe pharmacophores [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] was carried out, and it was found that the following requirements are advisable to obtain an analogue with reasonable activity:…”
Section: Resultsmentioning
confidence: 99%
“…A bibliographic search of the main ezetimibe pharmacophores [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] was carried out, and it was found that the following requirements are advisable to obtain an analogue with reasonable activity:…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the NPC1L1-mediated uptake of cholesterol, it has been reported that N-terminal domain of NPC1L1 binds cholesterol and promotes the formation of cholesterol-enriched microdomain in the plasma membrane to facilitate cholesterol transport [24,25]. In addition, recent cryo-electron microscopy structural analyses indicated that NPC1L1 forms a cholesterol-delivering tunnel from the N-terminal domain to the plasma membrane and that ezetimibe binds to the middle of the tunnel, resulting in the inhibition of cholesterol uptake [26]. As sphingolipids are colocalized with cholesterol in the plasma membrane [27], it is possible that NPC1L1 promotes the incorporation of sphingolipids, as well as cholesterol, into the plasma membrane to facilitate their transport.…”
Section: Discussionmentioning
confidence: 99%
“…Densities that correspond to cholesterol or its derivatives have been observed at different positions along the central tunnel (34)(35)(36)(37).…”
Section: Co-folded Loop1 and Loopmentioning
confidence: 99%
“…We submitted the poly-Ala model of the luminal domains L1/L7 to the Dali server to search for homologous structures (33). All the top ranking entries are of SSDcontaining proteins, including NPC1 (Niemann Pick disease, type C), NPC1L1 (NPC1like), NCR1 (NPC1-related), Ptch 1 (patched 1), and Disp (Dispatched) (34)(35)(36)(37)(38). This result was unexpected because our previous sequence blast failed to reveal sufficient similarities between the luminal/extracellular domains of Scap and the other SSDcontaining proteins (Fig.…”
Section: Co-folded Loop1 and Loopmentioning
confidence: 99%
See 1 more Smart Citation